Inovasi Kepemimpinan Kepala Daerah (Studi Kasus : Walikota Surabaya Ir. Tri Rismaharini, MT) - Muhammad Aulia Fachrudin; Teguh Yuwono (Journal of Politic and Government Studies, 2017)
Innovation for a local government is a necessity in attempt to achieve public prosperity and welfare.It is related to innovation based on the discussion with Surabaya mayor, Ir. Tri Rismaharini, MT whose well known by her innovations and creative ideas on building the city of Surabaya. This study attempts to analyse the role of female leader, the effectiveness of leadership, various forms of leadership, the processes, the key factors of success, obstacles of leadership in building innovation leadership of Surabaya mayor. Research methods used during this research is qualitative study, where the study conducted by the reasonable situation (natural setting). Research is done in the city of Surabaya, East Java. Research instrument by interviews, the literature study and documentations was done with sources of information chosen using certain consideration (purpose sampling) and source of information derived from various sources that associated with the problems. The results of innovation leadership of Surabaya mayor showed that there is an influence from the role of female leader in creating the effectiveness of leadership government in Surabaya. This could be seen in the pattern, prospective of nature affected on conduct leader who innovative and effective. In addition, also found key factors of success that bring up innovation program by approach humanistic leadership, communicative, discipline and transparent are able to increase public participation in innovation on regional development. Beside, also found the obstacles faced by the leader that have to solve clearly so innovation that produced not have only been contemporary but continuity and acceptable in all levels of society. The recommendations given to the head of government is the pattern of innovative and effective leadership that should keep developed, also every head of the governments must be able to accommodate the necessity of the society from all sectors such as governments, institutions, society, community and private so it will create the effective and innovative leadership synergy. Key Words: Leadership Government, the role of women, Leadership Innovation, the effectiveness of leadership, the head of regional government